An early history of compassion emotion and imagination in Hellenistic Judaism - Mirguet, Françoise 1980- (Cambridge New York, NY Port Melbourne Daryaganj, Delhi Singapore Cambridge University Press, 2017)
In this book, Françoise Mirguet traces the appropriation and reinterpretation of pity by Greek-speaking Jewish communities of Late Antiquity. Pity and compassion, in this corpus, comprised a hybrid of Hebrew, Greek, and Roman constructions; depending on the texts, they were a spontaneous feeling, a practice, a virtue, or a precept of the Mosaic law. The requirement to feel for those who suffer sustained the identity of the Jewish minority, both creating continuity with its traditions and emulating dominant discourses. Mirguet's book will be of interest to scholars of early Judaism and Christianity for its sensitivity to the role of feelings and imagination in the shaping of identity. An important contribution to the history of emotions, it explores the role of the emotional imagination within the context of Roman imperialism. It also contributes to understanding how compassion has come to be so highly valued in Western cultures
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Jews -- History -- 586 B.C.-70 A.D; Jewish literature -- History and criticism; Compassion; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D; Jews -- History -- 586 B.C.-70 A.D; Jewish literature -- History and criticism